Edukasi Masyarakat Mencegah Penularan Covid-19 di Cianjur - Risma Kusmiati; Dedi Junaedi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2021)
The thematic KKN 2020 Mekarjaya Village, Cikalongkulon District, Cianjur Regency, which has been held since November 16, 2020, has carried out this activity which consists of: socializing education on preventing Covid-19 transmission, counseling on healthy living, tutoring supported by fun learning media, watching educational videos as efforts to prevent transmission of Covid-19, implementing health protocols, making and distributing masks, making and spraying disinfectants, carrying out joint exercises, community service, and data collection and population grouping All programs, both individual and group, have been carried out well with the participation of the government and the community despite the many challenges faced in terms of resources and funds. Constraints in the form of challenges during KKN can be anticipated properly, for the success of various activities that have been planned in the work program and those that are not planned.